2013
DOI: 10.1177/1947601913485414
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinases and Their Role in Radiation Response

Abstract: Ionizing radiation, like a variety of other cellular stress factors, can activate or down-regulate multiple signaling pathways, leading to either increased cell death or increased cell proliferation. Modulation of the signaling process, however, depends on the cell type, radiation dose, and culture conditions. The mitogen-activated protein kinase (MAPK) pathway transduces signals from the cell membrane to the nucleus in response to a variety of different stimuli and participates in various intracellular signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(191 citation statements)
references
References 100 publications
5
183
0
3
Order By: Relevance
“…Mitogen-activated protein kinases (MAPKs) are the protein kinases involved in cell survival, such as cell proliferation, differentiation, migration, and apoptosis [152]. The types of known MAPKs are extracellular signal-regulated kinase 1 and 2 (ERK 1/2), ERK 5, JNK 1–3, and p38 protein isoforms (p38α, β, γ, and δ) [153].…”
Section: Mechanisms Of Action In Disease Preventionmentioning
confidence: 99%
“…Mitogen-activated protein kinases (MAPKs) are the protein kinases involved in cell survival, such as cell proliferation, differentiation, migration, and apoptosis [152]. The types of known MAPKs are extracellular signal-regulated kinase 1 and 2 (ERK 1/2), ERK 5, JNK 1–3, and p38 protein isoforms (p38α, β, γ, and δ) [153].…”
Section: Mechanisms Of Action In Disease Preventionmentioning
confidence: 99%
“…MAPK signaling includes the ERK, p38 MAPK and JNK pathways, and serves an important role in cell inflammation, apoptosis, proliferation and differentiation. MAPK signaling is activated by post-translational phosphorylation mediated by various kinases (11,12). Studies have shown that p38 MAPK and ERK pathways participate in the inflammation of endothelial cells, while JNK pathway does not function in this process (27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MAPK signaling is activated by post-translational phosphorylation mediated by various kinases (11,12). It has been demonstrated that MAPK signaling was activated in the rat lung tissue following CPB (13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been discovered that ATM indirectly induces AKT and ERK phosphorylation, and inhibiting the ATM kinase with an ATM-specific inhibitor was found to reduce the phosphorylation of AKT and ERK (30,31). Meanwhile, the phosphorylated ERK promotes ATM-dependent foci formation, making ATM and ERK signaling under the control of a regulatory feedback loop (32). Our findings showed that the total AKT and ERK did not change significantly after treatment while the phosphorylation of AKT and ERK was inhibited by β-elemene with increased concentrations.…”
Section: Discussionmentioning
confidence: 99%